Impasses e dificuldades nas formulações freudianas inaugurais sobre a psicose: uma abordagem retroativa de Lacan a Freud - Sueli Rodrigues Burgarelli (2007)
The starting point of this investigation is the strangeness that the reader of Sigmund Freuds work experiments before his out coming formulations on psychosis. It becomes notorious, throughout this dissertation, that, initially, Freud conceives psychosis with the same conceptual arsenal used on the treatment of neurotic symptoms in general. It aims, therefore, to show in what point the specificities of the psychotic subject are not directly contemplated on these out coming formulations. It emphasizes, particularly, insufficiencies of applicability of stress, peculiar to the effectual mechanism of hysterias and obsessions, to establish the differential clinic between the fields of neuroses and psychosis. It sticks out, on the other hand, the importance of using the elaborations contained on books 2 and 3 of Jacques Lacans Seminary as a way of foreseeing a possible formulization of the insufficiencies and concerning difficulties to the first formulations of the Freudian text about the mental functioning on the psychosis. This work, guides itself, as such, by the capital hypothesis that the specificity of such functioning demanded on Lacan a concise and systematic differentiation between the records of the imaginary and symbolic. It is known, for example, that the forclusions mechanism of the name-of-the-father, featured in the end of book 3 of the Seminary, The psychoses, claimed for developments and detailed explanations about the own way of autonomous functioning of the symbolic order. In short, the thesis of the autonomy of the significant regarding to the meaning on the production of signification, assumes a decisive place to the clearance of the concerning difficulties that hindered this founder moment of Freuds work of having the success on the metapsychologic elucidation of the specific mechanism of psychosis.